A Study on the Optimal Currency Structure of China’s Foreign Exchange Reserve: How Can China Make Trade-off between the Euro and the Dollar? - Xu, Feihong (2012)
China’s foreign exchange reserves accumulation has been boosted dramatically in recent years. However, this huge amount of $ 3.3 trillion reserves really worries Chinese government because of a potential substantial depreciation of the dollar. The emergence of the euro gradually shifts the currency portfolio from the dollar to euro. Just when people believe the euro is able to challenge the dollar as the primary reserve currency, however the euro suffers from a serious crisis. The competition between euro and dollar becomes even more violent. Each central bank is always seeking for an optimal currency composition of foreign exchange reserves. Previous studies (Ben-Bassat, 1980; Heller-Knight, 1979; Dooley, 1986) prove factors like risk-return considerations, international trade flows, debts servicing payments, transaction costs, and reference currency will have prominent impact on currency composition of foreign exchange reserves. The main results in this study include 1) The actually observed share of dollar is greater than that emerging from the optimization; 2) The current euro allocation is a slight higher than the optimal share, but it is suggested to keep the euro share at this level; 3) The Japanese Yen needs to be raised twice more from actual 8% -10% to the optimized 15%-25%; 4) the Swiss Franc is very close to the observed figure, the UK pound is undervalued and gold holding is strongly suggested to increase in this study.